2023
DOI: 10.1093/gji/ggad039
|View full text |Cite
|
Sign up to set email alerts
|

Transient core surface dynamics from ground and satellite geomagnetic data

Abstract: Summary We present an update of the geomagnetic data assimilation tool pygeodyn, use it to analyze ground and satellite-based geomagnetic datasets, and report new findings on the dynamics of the Earth’s outer core on interannual to decadal time-scales. Our results support the idea that quasi-geostrophic Magneto-Coriolis waves, recently discovered at a period of 7 years, also operate on both shorter and longer time-scales, specifically in period bands centered around 3.5 and 15 years. We revisit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 88 publications
2
4
0
Order By: Relevance
“…For wave-like motions with periods respectively [2 − 4.5]τ A and [6 − 13.5]τ A , we have estimated the outward wave velocity C to be about U A /10 and U A /15. We can compare these values with the geophysical estimate by Istas et al (2023). They found the wave velocity to be about 150 km/yr (U A /7) and 75 km/yr (U A /15) at periods about 7 yr (3.5 τ A ) and 15 yr (7.5 τ A ).…”
Section: Recovery Of Interannual and Decadal Changessupporting
confidence: 52%
See 2 more Smart Citations
“…For wave-like motions with periods respectively [2 − 4.5]τ A and [6 − 13.5]τ A , we have estimated the outward wave velocity C to be about U A /10 and U A /15. We can compare these values with the geophysical estimate by Istas et al (2023). They found the wave velocity to be about 150 km/yr (U A /7) and 75 km/yr (U A /15) at periods about 7 yr (3.5 τ A ) and 15 yr (7.5 τ A ).…”
Section: Recovery Of Interannual and Decadal Changessupporting
confidence: 52%
“…The changes in core angular momentum carried by geostrophic motions, as estimated from core surface velocities, do balance the changes in mantle angular momentum inferred from LOD data for periods ranging from ≈ 5 to 60 years (Jault et al, 1988;Jackson et al, 1993;Baerenzung et al, 2018;Gillet et al, 2019;Istas et al, 2023). The transfer of angular momentum between the core and the mantle is necessarily mediated by one or several torques, such as the electro-magnetic (EM), gravitational, pressure or possibly the viscous torque (Buffett, 1996;Jault, 2003;Roberts and Aurnou, 2012).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The new quasi-geostrophic (QG) magnetoinertial (Alfv én) and magneto-Coriolis waves exhibited that way could successfully explain the occurrence of geomagnetic jerks, or abrupt changes in the acceleration of Earth's magnetic field (Aubert & Finlay 2019 ;Aubert et al 2022 ). A tight interconnection between numerical and observational research also enabled the first theoretical characterization (Gerick et al 2021 ) and observation (Gillet et al 2022 ;Istas et al 2023 ) of rapid, QG magneto-Coriolis (QGMC) waves in core flows inferred from geomagnetic variations.…”
mentioning
confidence: 89%
“…(QGMC) waves. This scenario is further discussed by Istas et al (2023) through the inversion of the core flow using prior information from numerical dynamos. In summary, previous studies have suggested that geomagnetic jerks are likely associated with wave-like fluid motions within the Earth's core.…”
mentioning
confidence: 99%